The legend of Zelda. Twilight princess. 1 - Himekawa, Akira; Stan!, 1964- (VIZ Media, 2017)
An evil menace is on the hunt for Princess Midna in the hopes of gaining the power he needs to rule the Twilight Realm and the World of Light. And Link must fight the Kind of Shadows's minions who threaten the peaceful, quiet village he's made his home in.